HTTP blocking in MM: signal.org, twitter.com, whatsapp.com (Myanmar) - Voidly (2026)
WARNING severity censorship detected in Myanmar. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0007
Keywords: censorship; MM; censorship; warning